2016
DOI: 10.1128/mbio.01520-16
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Damage: Detrimental Effect of Antibiotics on the Development of Protective Immune Memory

Abstract: Antibiotic intervention is an effective treatment strategy for many bacterial infections and liberates bacterial antigens and stimulatory products that can induce an inflammatory response. Despite the opportunity for bacterial killing to enhance the development of adaptive immunity, patients treated successfully with antibiotics can suffer from reinfection. Studies in mouse models of Salmonella and Chlamydia infection also demonstrate that early antibiotic intervention reduces host protective immunity to subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 81 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…Intracellular pathogens like Salmonella cause high disease mortality and morbidity worldwide (3,41). Next-generation Vi capsular polysaccharide-conjugate typhoid vaccines are likely to enhance protection against Vi-expressing typhoid serovars, but will not combat systemic salmonellosis caused by Vi-negative paratyphoid or nontyphoidal serovars (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pathogens like Salmonella cause high disease mortality and morbidity worldwide (3,41). Next-generation Vi capsular polysaccharide-conjugate typhoid vaccines are likely to enhance protection against Vi-expressing typhoid serovars, but will not combat systemic salmonellosis caused by Vi-negative paratyphoid or nontyphoidal serovars (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Patients have history of other malignancies, or they have been previously treated with any anti-cancer agents, non-steroid antiinflammatory drugs (NSAIDs), or antibiotics. An infectious or inflammatory status, or the administration of specific agents to intervene such conditions would affect the accuracy of blood test, so patients with any record of these conditions mentioned above were excluded from this study [34][35][36][37]. (iii) Patients with incomplete medical records or laboratory results were also excluded.…”
Section: Patient Selectionmentioning
confidence: 99%
“…On the other hand, while early-life immune development has consequences that play out well into adulthood (32), antibiotic use in adulthood also may jeopardize protective responses to infectious agents (33). Benoun et al (33) have suggested that the therapeutic use of antibiotics may impair the formation of tissue-resident CD4 memory T cells by shortening the period of antigen presentation. Also, as we discuss later, antibiotics may have detrimental effects on vaccine responses (34).…”
Section: Microbiome and Immune System Developmentmentioning
confidence: 99%